RETRACTED: A dynamic relationship between renewable energy consumption, non-renewable energy consumption, economic growth and CO2 emissions: Evidence from Asian emerging economies - Zhang, Taiming; Yin, Jiemin; Li, Zhenghao; Jin, Yitong; Ali, Arshad; Jiang, Bin (Frontiers in Environmental Science, 2023)
This study aims to explore the relationship between renewable energy consumption, non-renewable energy consumption, carbon dioxide emissions and economic growth in China, India, Bangladesh, Japan, South Korea and Singapore using panel Augmented Mean Group (AMG) estimation techniques over the period 1975-2020. The results of the analysis show that renewable energy consumption, nonrenewable energy consumption, employed labor force, and capital formation contribute significantly to long-run economic growth. The study also found that non-renewable energy consumption significantly increased long-term carbon emissions, while renewable energy consumption significantly reduced long-term carbon emissions. GDP and GDP3 have a significant positive impact on environmental degradation, while GDP2 has a significant negative impact on environmental degradation, thereby validating the N-type EKC hypothesis in selected emerging economies. The countrywise AMG strategy records no EKC in India and Bangladesh, an inverted U-shaped EKC in China and Singapore, and an N-shaped EKC in Japan and South Korea. Empirical evidence from the Dumitrescue-Hurlin (2012) panel causality test shows that there is a two-way causality between renewable energy consumption and economic growth, supporting the feedback hypothesis. Strategically, empirical evidence suggests that higher renewable energy is a viable strategy for addressing energy security and reducing carbon emissions to protect the environment and promote future economic growth in selected Asian countries.